Oxidative Stress in Endometrial Flushing Fluid of Patients with Polycystic Ovary Syndrome, Endometrioma and Uterine Leiomyoma: Comparison with Healthy Controls - Mustafa Demir; Onur Ince; Bulent Yilmaz; Mert Ulas Barut; Ulviye Cansu Ozturk; Avni Kılıc; Ahmet Berkiz Turp; Recep Sutcu; Seyithan Taysi (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Polycystic ovary syndrome, myoma uteri and endometrioma are frequently seen gynecologic problems and all three diseases may cause infertility. Aim of this cross-sectional study was to compare total antioxidant status, ceruloplasmin, total sulfhydryl , total oxidant status, lipid hydroperoxide and oxidative stress index levels in endometrial flushing fluid of patients with Polycystic ovary syndrome (n=20), uterine leiomyoma (n=20), endometrioma (n=19), and healthy women (n=20).